2010
DOI: 10.1093/humrep/dep474
|View full text |Cite
|
Sign up to set email alerts
|

The enigmatic uterine junctional zone: the missing link between reproductive disorders and major obstetrical disorders?

Abstract: While there is a growing realization that the origins of major obstetrical complications associated with defective deep placentation, such as pre-term labour, fetal growth restriction and pre-eclampsia, may lie in the very early pregnancy events, the underlying mechanisms are not understood. Impaired deep placentation is foremost a vascular pathology, characterized by a lack of endovascular trophoblast invasion and remodelling of a segment of the spiral arteries embedded within the inner myometrium of the uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
85
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 39 publications
7
85
0
7
Order By: Relevance
“…22 As the thickening and disruption of the junctional zone appearance is strongly associated with uterine adenomyosis, adenomyosis might be related to placental insufficiency and poor placental perfusion, resulting into PIH. 4 Our results also showed that the incidence of FGR (11.8%; 31/262) was higher than that reported in the general population (5%-10%). 23 FGR cases of adenomyosis-complicated pregnancy with poor placental blood flow were reported.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…22 As the thickening and disruption of the junctional zone appearance is strongly associated with uterine adenomyosis, adenomyosis might be related to placental insufficiency and poor placental perfusion, resulting into PIH. 4 Our results also showed that the incidence of FGR (11.8%; 31/262) was higher than that reported in the general population (5%-10%). 23 FGR cases of adenomyosis-complicated pregnancy with poor placental blood flow were reported.…”
supporting
confidence: 65%
“…During pregnancy, the invasion of trophoblasts into the endometrium and the myometrial junctional zone causes decidualization and unique vascular changes. 4 The thickening and disruption of the junctional zone in women with adenomyosis might be associated with placental insufficiency and complications of pregnancy. In addition, the type of adenomyosis is considered to be an important factor affecting decidualization and placentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic endometriosis, especially in severe stages, is also strongly associated with junctional zone thickening [73,74,83,84]. Observational studies suggest that perturbations in junctional zone structure or functions before conception predispose towards a spectrum of fertility and obstetrical complications [85].…”
Section: The Endo-myometrial Junctional Zonementioning
confidence: 99%
“…Процессу инвагинации эндометри-альной ткани способствуют нарушения регуляции молеку-лярных механизмов апоптоза, пролиферации, неоангио-генеза и экспрессии матриксных металлопротеиназ [13]. Данные трансмиссионной электронной микроскопии, иммуногистохимического окрашивания для Cadherin, иммунофлюоресценции для CD45 и CD68 подтверждают, что ультрамикротравма в зоне эндомиометриального перехода (junctional zone) является одним из ключевых звеньев патогенеза аденомиоза [14].…”
unclassified